The Impact Of Entrepreneurial Competencies On UMKM - Mustikowati, Rita Indah; Sari, Ati Retna; Afian, Affan; Fachthurrohim, Muchammad (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
The purpose of this article is to present a detailed analysis of the entrepreneurial competence literature that has been published in international journals from 2012 to 2021, determining the intellectual structure of the field of entrepreneurial competence and its maturity as an academic field of study. This article uses a quantitative methodology for literature study, i.e. bibliometric analysis, relevant papers were obtained from Scopus database retrieved on Monday, November 8, 2021, 9.09 pm. A total of 669 papers were identified and studied for bibliometric analysis. The study identified a significant increase in scientific investigation of entrepreneurial competence in recent years, along with greater collaboration and international research. It was demonstrated that some countries dominate the entrepreneurial competence research area, such as Spain and the United Kingdom, whereas institutional and individual research results are spread more evenly. It was also found that authors or institutions dominate the entrepreneurial competence literature. The epistemological orientation shows that the published literature is mostly theoretical and descriptive. This article makes important contributions. First, it presents the intellectual structure of entrepreneurial competence as a discipline. Second, it determines the current maturity of the field based on its epistemological orientation, concluding that entrepreneurial competencies are maturing, with theory development followed by empirical testing and validation resulting in increasing consensus on the boundaries of the field..